IDENTIFIKASI CACAT LASAN FCAW PADA FONDASI MESIN KAPAL MENGGUNAKAN METODE ULTRASONIC TESTING - Widyawati, Fauzi; Marano, Lino (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Ultrasonic testing is one of the non-destructive inspection methods for welding results. The ultrasonic testing method has several advantages, namely it can be used to analyze the position of the defect in the object, both the depth of the defect and the dimensions of the defect, and it is an environmentally friendly method. Physical defects that are in solid objects of course cannot be known from direct vision so it is necessary to carry out an inspection of an object to see whether or not there are defects that occur in solid objects. Ultrasonic testing of the results of FCAW welding on the foundation of the ship's engine. FCAW welding is applied to the foundation with two types of welding positions, namely the overhead position coded P1 and the horizontal position coded P2. The test was carried out using a wave frequency of 4 MHz and using a 0Â° probe for analysis of defects in the area around the weld metal and a 70Â° probe for analysis of the weld metal. The tests were carried out using the ASME section V and ASTM E164 standards as the standard for determining defects. The test results at the P1 welding position found two types of defects, namely incomplete fusion defects with five welding points with the longest defect length of 40mm and porosity defects with two points with the longest defect length of 30mm. While the results of ultrasonic testing at the P2 welding position found two types of defects, namely slag inclusion defects with a defect length of 35mm and incomplete penetration defects with a defect length of 20 mm. The conclusion of ultrasonic testing is that the difference in welding positions is that the welding position greatly affects the quality of the welding results. The defects resulting from the welding position also vary.